The Effectiveness Of School Principals' Academic Supervision Management On The Competency Of Junior High School Teachers In Seunagan District - Ida Deliana; Niswanto Niswanto; Bahrun Bahrun (JETL (Journal of Education, Teaching and Learning), 2024)
The importance of teacher competency lies in the teacher's ability to deliver effective learning, inspire students, and help teachers reach their maximum potential. Therefore, the role of the school principal, especially in academic supervision, is very important to support increasing competency and quality of learning in schools. This research aims to find out whether the principal's academic supervision management is effective in improving the competence of junior high school teachers in Seunangan District. This research uses quantitative methods. The subjects in this research consisted of 3 school principals and 3 class teachers, each of whom came from 3 schools, namely SMPN 1 Seunagan, SMPN 3 Seunagan and SMPN 6 Seunagan selected using saturated sampling techniques. Data collection techniques in this research used observation, interviews and questionnaires. The analysis technique in this research uses normality, homogeneity and T tests. The results of this research show that the principal's academic supervision management has an effective effect on teacher competence with the t test results having a significance value of less than 0.05. Therefore, the implementation of academic supervision management by school principals to improve teacher competence is effective.